2006
DOI: 10.4038/jas.v1i1.8089
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of charcoal-cement passive evaporative cooler for banana ripening

Abstract: The common banana ripening methods practiced by fruit sellers are application of calcium carbide or 'ethrel'. Ethrel is expensive and therefore the ethylene analogue calcium carbide is commonly used although it contains heavy metals as it is readily available. Therefore a passive evaporative cooler made of charcoal, cement and sand was tested as a ripening chamber for banana as the internal relative humidity and temperature were ideal for banana ripening. The evaporative cooler maintained a high relative humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
7
7
0
Order By: Relevance
“…The longest delay in colour change was observed in fruits treated with 1-MCP and placed in perforated polyethylene in which the fruits were just at full yellow colour stage on the last date of storage (28 days). The peel colour development from green to yellow (stages 1 to 6) in this study is in agreement with the 1 to 2 weeks duration reported before (Siriboon and Banlusilp, 2004;Dharmasenal and Kumari, 2005;Salvador et al, 2006). The conversion of green colour of the peel into yellow as a result of chlorophyll degradation is an indicator of senescence that is enhanced by high rate of respiration which in turn is regulated by temperature, ethylene, O 2 and CO 2 gases (Pinto et al, 2004).…”
Section: Peel Colour Changesupporting
confidence: 93%
See 3 more Smart Citations
“…The longest delay in colour change was observed in fruits treated with 1-MCP and placed in perforated polyethylene in which the fruits were just at full yellow colour stage on the last date of storage (28 days). The peel colour development from green to yellow (stages 1 to 6) in this study is in agreement with the 1 to 2 weeks duration reported before (Siriboon and Banlusilp, 2004;Dharmasenal and Kumari, 2005;Salvador et al, 2006). The conversion of green colour of the peel into yellow as a result of chlorophyll degradation is an indicator of senescence that is enhanced by high rate of respiration which in turn is regulated by temperature, ethylene, O 2 and CO 2 gases (Pinto et al, 2004).…”
Section: Peel Colour Changesupporting
confidence: 93%
“…The low storage room relative humidity (35 to 58%), in addition to possible respiratory loss, could have aggravated the weight loss at ambient while in other treatments either of these causes might have been affected. This result corresponds with the weight loss value reported by Dharmasenal and Kumari (2005) for fruits stored under open ambient condition for the same period. The lower weight loss obtained from fruits placed in polyethylene bags with perforation compared to those in non-perforated ones could be due to removal of ethylene which has a catalytic role in increasing respiration (Jobling, 2000) while also maintaining RH in the package thus reducing water loss.…”
Section: Physiological Weight Losssupporting
confidence: 90%
See 2 more Smart Citations
“…In all treatments the percentage weight loss increased with the storage time and ripening progressed, which possibly resulted from transpiration and respiration of the fruits. Energy produced from the respiration process in the form of heat is released from the fruit by evaporation of water causing a weight loss (Dharmasena and Kumari 2005). Loss in weight by various treatments also has also been reported by Mahajan et al (2010) in banana cv.…”
Section: Results and Discussion:-mentioning
confidence: 76%